Contextual factors influencing physicians’ perception of antibiotic prescribing in primary care in Germany: a prospective observational study - Queder, Annika; Arnold, Christine; Wensing, Michel; Poß-Doering, Regina (BMC health services research, 2022)
Antimicrobial resistance is a worldwide challenge for health services and systems alike. To reduce the overuse of antibiotics, multifaceted interventions are often used to achieve sustainable effects. It can be assumed that these effects are influenced by contextual factors. Embedded in the cluster randomized trial ARena (Sustainable reduction of antibiotic-induced antimicrobial resistance), the aim of this present study was to identify contextual factors associated with practitioners’ perceptions of antibiotic prescribing in German primary health care.
Gesehen am 07.04.2022